Rapid establishment and stable performance of a new algal-bacterial granule system from conventional bacterial aerobic granular sludge and preliminary analysis of mechanisms involved. (April 2020) - Zhang, Yihao; Dong, Xiaochuan; Liu, Sen; Lei, Zhongfang; Shimizu, Kazuya; Zhang, Zhenya; Adachi, Yasuhisa; Lee, Duu-Jong
Graphical abstract: Highlights: Rapid transformation from bacterial granules to algal-bacterial ones was realized. Mature algal-bacterial aerobic granular sludge (AGS) was achieved within 18 days. The new algal-bacterial AGS system averagely removed 66% of TN and 64% of TP. Algae content was a good indicator for the maturation of algae-bacterial granules. Abstract: This work proposed a promising method to rapidly establish stable algal-bacterial aerobic granular sludge (AGS) system from conventional bacterial AGS. It was realized in this study within 18 days by inoculating 4.3% (w/w, dry mass basis) of mature algal-bacterial AGS into a sequencing batch reactor with conventional bacterial AGS treating synthetic domestic wastewater. The newly established algal-bacterial AGS reactor (RA-B ) exhibited better performance in nutrients removal, averagely 66.21 ± 5.18% of total nitrogen (TN) and 63.96 ± 6.00% of total phosphorus (TP) in comparison to 53.36 ± 2.37% and 48.87 ± 7.79% by the conventional bacterial AGS reactor (RB ), respectively. Better AGS settleability indicated by sludge volume index (SVI30 ) was also noticed in RA-B (45.48 ± 0.92 ml/g versus 71.30 ± 3.03 ml/g in RB ) on day 25. Most importantly, under the same operation strategy, the algal-bacterial AGS in RA-B well maintained its granular stability and became dense and compact, while the bacterial AGS (RB ) collapsed to a large extent during the final stage of 25 days' operation. Algae content was found to be a good indicator of the maturation of newly formed algal-bacterial AGS. In this study, preliminary analysis was also conducted on the mechanisms involved in the rapid formation of algal-bacterial AGS and the changes of its biological communities.